(untitled) (Global Journal of Science Frontier Research, 2018)
There is much agreement in theoretical particle physics that black holes (BH) exist not only at massive galactic scales but also at the subatomic Planck scale, Planck Virtual Black Holes (PVBH). It is very possible that white holes (WH) exist there as well, both are predicted to exist from Einstein’s General Relativity Theory (GR). "The possibility of the existence of white holes was put forward by Russian cosmologist Igor Novikov in 1964. White holes are predicted as part of a solution to the Einstein field equations known as the maximally extended version of the Schwarzschild metric" according to Wikipedia. Working in a quantum field dynamic of Planck-foam interconnected wormholes, these enigmatic (GR) derived organs of virtual Planckian origin, create the cyclical flux of the energy/information of baryonic matter (BM) across the baryonic matter/dark matter membrane barrier of two different worlds; while creating the virtual particles required for organic as well as inorganic reality. This highly energetic thermodynamic zone seems to exhibit reverse entropy as PVBH’s produce cyclical energy/information as BM is consumed, conserved, and recycled through WH dynamics creating a memory of nature through a feedback loop process I call biomorphic transradiation. The philosophical implications of this phenomena are staggering but in this paper I will focus on the thermodynamic reassessment of entropy to be considered.